Screening of jute and kenaf varieties for salinity tolerance - isfatuzzaman Bhuyan, Md.; M. Mehadi Hassan, K; Jahan Lipi, Nowrose; Rafiq Uddin, Md; Monirul Islam, Md; Ferdous, Mahbuba; Hasan Antor, Nazmul; Das, Parna (International Journal of Advanced Geosciences, 2018)
A study was conducted in the Department of Agronomy, Bangladesh Agricultural University (BAU), Mymensingh from April to August 2012 to examine the salinity tolerance of eight jute varieties (CVE-3, C-83, CVL-1, BJC-7370, O-795, O-9897, OM-1, O-72) and two kenaf varieties (HC-95 and HC-2). Initially germination of these varieties were evaluated under six salinity levels viz. 0mM, 20mM, 40mM, 60mM, 80mM, and 100mM NaCl in the seed laboratory of the Department of Agronomy. Afterwards, all the varieties was grown in pots in the net house under four salinity levels viz. 0mM, 25mM, 50mM, and 75mM. The results from the germination study revealed that under control condition (0mM NaCl) all the jute varieties showed germination more than 80% both at 7 and at 14 days after seed sowing, whereas kenaf varieties had germination a little less than 80%. Among the jute varieties, O-72 showed the highest germination (92%), which was statistically similar with those of OM-1(91%), O-795 (90%), and C-83(87%). Salinity stress decreased germination drastically in all of the jute and kenaf varieties. A salinity level of 100mM caused the highest germination inhibition (74.70%) in jute variety CVL-1, which was very close to those of BJC-7370 and O-72. On the other hand, the lowest germination inhibition (51.11%) was recorded in jute variety O-795. The results of the pot trail showed that the plant characters of jute and kenaf varieties were affected significantly by salinity stress. All the varieties produced their respective plant height, number of leaves per plant, and plant dry weight under control condition (no salinity). Among these varieties, CVE-3 produced the highest plant height (145.2cm), and total dry weight (22.55g), whereas O-72 produced the highest number of leaves per plant (24.67). All these plant characters decreased sharply due to salinity stress irrespective of variety. However, the rate of decrease of plant characters occurred differentially in the jute and kenaf varieties. The highest rate of decrease in number of leaves (74.22%) was found from the variety CVE-3, whereas the lowest one was recorded from the variety HC-2 (51.68%). Salinity stress caused the highest decrease in total plant dry weight (73.68%) in the variety CVL-1 and plant height (73.64%) also in the variety CVL-1. On the contrary, the lowest decrease in plant dry weight (50.99%) was found in the variety O-9897 and plant height also in variety O-9897 (50.88%). Based on the results from germination test and pot trail, it can be inferred that jute variety O-9897 appeared to be the most salt tolerant followed by O-795, HC-2, HC-95, CVE-3, O-72, C-83, BJC-7370, OM-1, and CVL-1.Â Â Â Â